Model Implementasi Kebijakan Pelayanan Administrasi Terpadu Kecamatan (PATEN) di Kabupaten Pidie Jaya - Muhammad Adril; Joni Dawud; Hendrikus T Gedeona (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2021)
Today's public service has become an increasingly strategic issue because the quality of the performance of the bureaucracy in providing public services has broad implications in social life. Changes in understanding that position the local government as a public servant, should be followed by the revitalization of the District through the implementation of the District Integrated Administration Service (PATEN) with the aim of improving community welfare and increasing the effectiveness of the District organization in public services. Based on the Regulation of the Minister of Home Affairs Number 4 of 2010, the District Integrated Administration Service (PATEN) is an effort to improve service quality in the context of bringing closer, easier and faster services to the community as well as making the sub-district a community service center and service node for integrated licensing service office/agencies in the district. Pidie Jaya Regency in implementing PATEN refers to the delegation of part of the Regent's authority to the sub-district head in the field of licensing and non-licensing which is regulated through Pidie Jaya Regent Regulation Number 15 of 2010 and Pidie Jaya Regent Regulation Number 19 of 2018 Concerning Service Standards and Job Descriptions of Inner District Personnel Implementation of Integrated Administrative Services in Inner District Pidie Jaya Regency. This study aims to formulate a model for the implementation of the PATEN implementation in Pidie Jaya Regency. The results showed that the implementation of the PATEN policy in Pidie Jaya Regency has not run optimally. To solve the problem of implementing the PATEN policy in Pidie Jaya Regency, researchers formulated a model for implementing transformation performance efforts that affect policy performance which includes strengthening sub-district institutions as PATEN implementation organizations, increasing human resource capacity, fulfilling facilities and infrastructure for supporting policies and implementing monitoring and evaluation of policies.